2009
DOI: 10.1186/1471-2164-10-298
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome expression analysis within the angiotensin II-apolipoprotein E deficient mouse model of abdominal aortic aneurysm

Abstract: Background: An animal model commonly used to investigate pathways and potential therapeutic interventions relevant to abdominal aortic aneurysm (AAA) involves subcutaneous infusion of angiotensin II within the apolipoprotein E deficient mouse. The aim of this study was to investigate genes differentially expressed in aneurysms forming within this mouse model in order to assess the relevance of this model to human AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
95
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 37 publications
8
95
1
Order By: Relevance
“…Various studies in humans and animals have shown the implication of UCNs in different cardiovascular disorders, such as atherosclerosis, myocardial infarct and heart failure [97,99,100]; however, its role on AAA has only been reported very recently [101,102]. The first evidence associating the UCNs to AAA was documented by Rush et al [102].…”
Section: Urocortinmentioning
confidence: 95%
See 2 more Smart Citations
“…Various studies in humans and animals have shown the implication of UCNs in different cardiovascular disorders, such as atherosclerosis, myocardial infarct and heart failure [97,99,100]; however, its role on AAA has only been reported very recently [101,102]. The first evidence associating the UCNs to AAA was documented by Rush et al [102].…”
Section: Urocortinmentioning
confidence: 95%
“…Using the Ang II-infused ApoE-/-mouse AAA model, they investigated genes that were differentially expressed in the aneurysm prone segment of aorta. Interestingly, UCN3 gene expression was downregulated in the suprarenal region of the aorta (susceptive to aneurysm formation in mice) compared to the infrarenal region (resistant to aneurysm formation in mice) [102], raising the speculation that UCNs have a protective function against AAA. In another study, the same group reported that UCN2 and CRFR2 gene expression were significantly higher in the most dilated part of the human AAA compared to the non-dilated proximal neck of the AAA [101].…”
Section: Urocortinmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence published to date relates to the aorta. In an angiotensin IIeinduced mouse model of abdominal aortic aneurysm, the aneurysm-prone segment showed increased Tgf-b expression, 31 and systemic neutralization of the Tgf-b activity markedly accelerated the progression of the aneurysm and its complications. 32 In a mouse model of aortic stenosis and heart failure induced by aortic banding, there was increased Tgf-b signaling, and treatment with SM16ddespite reducing myocardial fibrosis and ameliorating functiondeventually accelerated the death of the mice by causing aortic rupture at the banded site.…”
Section: Discussionmentioning
confidence: 99%
“…46 Microarrays and real time PCR will be used to assess circulating cell markers as previously described. 47 Ultrasound measurements will be undertaken at entry and 24 weeks by experienced sonographers within the vascular laboratories at each study centre. The sonographers will measure the maximum diameters of the infrarenal aorta perpendicular to blood flow while the participant is in supine and lateral decubitus position.…”
mentioning
confidence: 99%